Criminal Liability of Influencers as Online Gambling Affiliates from the Perspective of Information Technology Law - Anggita Dwi Rahayu; Laily Maghfiroh; Syana Mifta Salsabila; Syifadilla Subagyo Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of information technology has significantly transformed commercial practices and communication, including the growing prevalence of online gambling promoted on social media by influencers or affiliators. This phenomenon raises legal concerns because such promotions constitute the distribution of gambling-related information, which is explicitly prohibited under Article 303 of the Indonesian Criminal Code (KUHP) and Article 27(2) jo. Article 45(3) of the Electronic Information and Transactions Law (UU ITE). This study aims to analyze the form of criminal liability imposed on influencers acting as online gambling affiliators and examine the application of criminal provisions under the UU ITE in relation to their involvement. Using a normative juridical method with statutory and conceptual approaches, this research finds that any affiliator who intentionally uploads, distributes, or provides access to online gambling websites may be held criminally liable unless a valid excuse eliminates their culpability. Paid promotional activities indicate intent, thereby fulfilling the element of unlawfulness and allowing the perpetrator to be charged based on their level of involvement, whether under Article 303 of the KUHP or the provisions of the UU ITE. However, the enforcement of criminal sanctions remains challenging, particularly in the evidentiary process, as it relies heavily on the validity of electronic evidence such as transaction records, social media uploads, or other digital traces. The absence of detailed technical guidelines for the collection and examination of digital evidence hampers optimal investigation and prosecution